The Influence of GDP and Human Development Index on the Number of Poor People in Districts/Cities in North Sumatra Province - Handayani, Siti Alifah; Ardhana, M Bagas; Amanda, Dhea; Syarifah, Syarifah; Hidayat, Nasrullah (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This research aims to explore the relationship between Gross Regional Domestic Product (GRDP) and Human Development Index (HDI) on the number of poor people in districts/cities in North Sumatra Province in the 2018-2022 period. GRDP and HDI are used as economic and social indicators to understand the impact of economic growth and human development on poverty levels. Poverty is caused by limited access to basic needs, education and employment opportunities. This research uses a quantitative approach with secondary data and E-Views 12 software for analysis. The results of the analysis show that GRDP has a positive and significant influence on the number of poor people, while HDI does not have a significant influence. Income distribution and government policies need to be considered to reduce inequality in income distribution and improve community welfare evenly.